Cycling in primary progressive multiple sclerosis (CYPRO): study protocol for a randomized controlled superiority trial evaluating the effects of high-intensity interval training in persons with primary progressive multiple sclerosis - Kupjetz, Marie; Joisten, Niklas; Rademacher, Annette; Gonzenbach, Roman; Bansi, Jens; Zimmer, Philipp (Technische Universität Dortmund, 2023)
Background: Primary progressive multiple sclerosis (PPMS) is the least prevalent multiple sclerosis (MS) phenotype. For persons with PPMS (pwPPMS), pharmacological treatment options are limited. As a complementary non-pharmacological treatment, endurance training improves the health-related quality of life (HRQoL), numerous MS symptoms, and MS-related performance impediments. High-intensity interval training (HIIT) has been shown to induce superior effects compared to moderate-intensity continuous training (MCT). As current evidence is based on MS samples with mixed phenotypes, generalizability to pwPPMS remains unclear. Methods: CYPRO is a parallel-group, single-center, and single-blind randomized controlled superiority trial evaluating the effects of HIIT compared to MCT in pwPPMS. Sixty-one pwPPMS are randomized (1:1) to perform volume-matched HIIT or MCT sessions on bicycle ergometers two to three times per week in addition to standard rehabilitative care during their three-week inpatient stay at Valens rehabilitation clinic, Switzerland. Standard rehabilitative care comprises endurance and strength training, physiotherapy, and occupational therapy. HIIT sessions include six 90-second intervals at 95% peak heart rate (HRpeak), interspersed by 90-second active breaks with unloaded pedaling, aimed to reach 60%HRpeak. MCT represents the standard treatment at Valens rehabilitation clinic and is performed as continuous cycling at 60%HRpeak for the duration of 26 minutes. The primary outcome is cardiorespiratory fitness, assessed as peak oxygen consumption (V̇O2peak) during cardiopulmonary exercise testing (CPET). Secondary outcomes include peak power output during CPET, walking capacity, cognitive performance, HRQoL, fatigue, anxiety and depressive symptoms, and blood-derived biomarkers (e.g., serum neurofilament light chain, glial fibrillary acidic protein, kynurenine pathway metabolites) related to MS pathophysiology. All outcomes are assessed at baseline and discharge after three weeks. Venous blood sampling is additionally performed immediately and two hours after the first HIIT or MCT session. Discussion: CYPRO will expand current knowledge on symptom management and rehabilitation in MS to the subpopulation of pwPPMS, and will contribute to the exploration of potential disease-modifying effects of endurance training in MS. The superiority design of CYPRO will allow deriving explicit recommendations on endurance training design in pwPPMS that can be readily translated into clinical practice. Trial registration: CYPRO has been prospectively registered at ClinicalTrials.gov on 8 February 2022 (NCT05229861).
BMC neurology;23
Keywords: Multiple sclerosis; Primary progressive multiple sclerosis; High-intensity interval training; Physical fitness; Cardiorespiratory fitness; Serum neurofilament light chain; Glial fibrillary acidic protein; Kynurenine pathway; 796